2013
DOI: 10.1016/j.neulet.2013.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Acute working memory improvement after tDCS in antidepressant-free patients with major depressive disorder

Abstract: Based on previous studies showing that transcranial direct current stimulation (tDCS), a non-invasive brain stimulation technique that employs weak, direct currents to induce cortical-excitability changes, might be useful for working memory (WM) enhancement in healthy subjects and also in treating depressive symptoms, our aim was to evaluate whether tDCS could acutely enhance WM in depressed patients. Twenty-eight age- and gender-matched, antidepressant-free depressed subjects received a single-session of acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
2
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 44 publications
2
85
2
5
Order By: Relevance
“…Our findings in MDD patients are in accordance to previous literature showing that tDCS increased performance in the n-back task [16], ameliorated emotional inhibitory control [28], enhanced performance in the Emotional Stroop Task [8] and in the affective go/no-go task [2]. Thus, tDCS effects in depression might not be limited to the DLPFC, but also extends to the broader cortico-subcortical network associated with cognitive dysfunction in MDD and regulation of emotionally loaded information processing.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings in MDD patients are in accordance to previous literature showing that tDCS increased performance in the n-back task [16], ameliorated emotional inhibitory control [28], enhanced performance in the Emotional Stroop Task [8] and in the affective go/no-go task [2]. Thus, tDCS effects in depression might not be limited to the DLPFC, but also extends to the broader cortico-subcortical network associated with cognitive dysfunction in MDD and regulation of emotionally loaded information processing.…”
Section: Discussionsupporting
confidence: 92%
“…TDCS is a non-invasive neuromodulatory technique that employs weak direct currents (0.5-2 mA) to modulate brain activity [4] by regulating the frequency of action potentials triggered in the neuronal network [3]. Previous reports demonstrated that anodal tDCS over the DLPFC exerts beneficial effects in cognitive tasks [5], although most of them were methodologically limited [7,16,24,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding sham procedures, sham tDCS was performed using a procedure in which the electric current was turned off shortly after stimulation onset, although this short period ranged from 5 to 60 (Oliveira et al, 2013)seconds.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Regarding blinding, half of the studies were double-blinded (Barr et al, 2013;Gaudeau-Bosma et al, 2012;Guse et al, 2013;Keeser et al, 2013;Oliveira et al, 2013;Teo et al, 2011) and the other half were double single-blinded, i.e., the subject and the evaluator were blinded to the allocation group, but not the person applying the stimulation. The time period between stimulation conditions ranged from at least one hour to more than one week (Mulquiney, Hoy, Daskalakis, & Fitzgerald, 2011).…”
Section: Quality Assessmentmentioning
confidence: 99%